3, 4‐Diaminomaleimide Dyes – Simple Luminophores with Efficient Orange‐Red Emission in the Solid State. Issue 6 (13th February 2018) - Imoto, Hiroaki; Fujii, Ryosuke; Naka, Kensuke
Abstract : Maleimides have been utilized from materials science to biochemistry. In particular, maleimide‐based luminescent dyes have attracted much attention. Recently, we reported arylaminomaleimide dyes that exhibit effective blue‐green emission in the solid state. In this work, 3, 4‐diaminomaledimides were synthesized by simple and facile routes, and the obtained dyes show orange‐red emission due to the two amino groups. Notably, the dyes possess very simple structures, which are composed of only C, H, N, and O and minimal aromatic rings. Additionally, their emission intensities were enhanced in the solid state compared with those in solution. Theoretical calculations and X‐ray diffraction analyses supported our understanding of the emission behavior. Abstract : 3, 4‐Diaminomaleimides, composed of only C, H, N, and O and minimal aromatic rings, showed efficient orange‐red emission in the solid state. Furthermore, these dyes show aggregation‐induced emission enhancement.